314 LONG-TERM QUALITY OF LIFE FOLLOWING TRANSTHORACIC AND TRANSHIATAL ESOPHAGECTOMY FOR ESOPHAGEAL CANCER. (14th September 2020) - Jezerskyte, E; Saadeh, L; Hagens, E; Sprangers, M; Noteboom, L; van Laarhoven, H; Eshuis, W; Hulshof, M; van Berge Henegouwen, M; Gisbertz, S
Abstract: : Both a transthoracic (TTE) and a transhiatal (THE) esophagectomy may be possible in patients with a distal esophageal or gastroesophageal junction (GEJ) cancer. A number of studies report conflicting results in long-term health-related quality of life (HR-QoL) following these operations. This study investigates long-term HR-QoL in TTE and THE in a tertiary referral center. Methods: Disease-free patients after a TTE or THE for distal esophageal or GEJ carcinoma with a follow-up >2 years were included. Patients who visited the outpatient clinic of a tertiary referral center in the Netherlands between 2014–2018 were asked to complete the EORTC QLQ-C30 and EORTC QLQ-OG25 questionnaires. Outcome measures were all 31 HR-QoL domains. Results: During the study period, 132 patients underwent a TTE and 56 a THE. A better HR-QoL score was found for "problems with hair loss" (mean score 85.0 vs 114.4, p = 0.016) following TTE. Patients after minimally invasive TTE had better scores in ´physical functioning´ compared to minimally invasive THE (mean score 103.2 vs 88.6, p = 0.020). Patients following neoadjuvant therapy and TTE reported better "social functioning" compared to patients after neoadjuvant therapy and THE (mean scores 76.1 vs 59.9, p = 0.040). Conclusion: Long-term HR-QoL results are largely comparable in disease-free patients following TTE or THE for distal esophageal or GEJ carcinoma. Some domains in the whole cohort and in subgroups differed at the advantage of a TTE. These findings may aid in providing information to esophageal or GEJ cancer patients on what can be expected following treatment.